Travel broadens the mind - Vlismas, Emily (Trinity College Dublin, School of Languages, Literature and Cultural Studies, 2024)
The texts of my portfolio follow the theme of travel, exploration and journeys, starting from the thirteenth century and finishing in the twentieth century. The texts are ordered not by their published date of the source version used, but rather by when the first version was written (e.g., ST 2) or the era it is written about (e.g., ST 8). The title, Travel Broadens the Mind, was chosen because, in one way or another, each ST discusses a journey. And as indicative of the saying, the experience of all journeys affects our understanding of the world or ourselves in various ways. The first text, Dante’s Vita Nuova, depicts him pondering the frailty of life’s journey that brings him to travel through a vision or hallucination of Beatrice’s death, leaving him distraught. Text two, an excerpt from Marco Polo’s Il Milione, naturally recounts his exploration of and wonder at the new sights and experiences. In this section, he recounts the society in which Kaidu and his daughter live, as well as a geographic description of the land and the history of the Khan and Kaidu’s feuds. The third and fourth texts are about the Spanish conquest of Mexico: one recounts the devastation and destruction left in their wake, depicting the negative effect on the natives due to the colonists’ exploration; and the other describes the traditions of Aztec celebrations, as told by a Spanish friar to recount what he experiences there. Text five tells of an expedition by a Welshman to find evidence of an indigenous group in America with Welsh origins, but this journey leaves him disappointed to the point of alcoholism. The sixth text is a mock eighteenth-century diary entry of a failing, rambling poet who goes on a Grand Tour of Europe to bring about creative inspiration, without success.